Embracing Green Choices: Sentiment Analysis of Sustainable Consumption - Cubukcu Cerasi, Ceren; Balcıoğlu, Yavuz Selim; Kilic, Asli; Huseynov, Farid (ISRES Publishing, 2023)
Currently, resource scarcity and climate change are among the main global problems. Governments are actively seeking regenerative solutions so that humans and nature can co-exist in harmony in the face of ecological destruction and resource limitations. One of these solutions is green consumption. Making greener consumption decisions is necessary for society to become sustainable. If sustainable consumption is to be promoted, public perception must shift, and achieving this shift will be simpler if society's shift toward green consumption is understood. This research aims to explore the sentiment and attitudes towards sustainable consumption on YouTube, a popular online platform with a vast pool of user-generated content. We employ a combination of data mining techniques and sentiment analysis to process and analyze a large dataset of YouTube videos and comments related to sustainable consumption topics. The data collection includes videos from various categories, such as reviews of eco-friendly products, vlogs of sustainable living, and informative content on environmentally responsible practices. The study focusses on understanding user engagement, sentiment polarity, and the factors influencing positive or negative attitudes toward sustainable consumption. In this way, the attitude of society toward green consumption and the role of social networks in public opinion can be understood. Overall, the study shows how data mining techniques and social networks have the potential to help with the shift to more sustainable growth paths. © 2023 Elsevier B.V., All rights reserved.
International Conference on Research in Engineering, Technology and Science, ICRETS 2023 -- Budapest -- 303069
Keywords: Data mining; Green consumption; Sentiment analysis; Social media; Sustainability